2008
DOI: 10.1002/app.29053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal aging on the electrical properties of crosslinked polyethylene

Abstract: This article reports on the effect of thermal aging on the electrical properties of crosslinked polyethylene (XLPE) used in high voltage cables. It was shown that thermal aging modifies the electrical properties of the polymer. The degradation is accelerated when the temperature is increased. This degradation is due to a thermooxidation, followed by a loss of antioxidant, and a change in color of the material. At 80 and 100 C, the antioxidant is practically efficacious during the aging, whereas at 120 and 140 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…This has also seen by other workers, e.g. [46]. The cables were obviously oxidised and the increase in conductivity may be due to the molecular bonds being weakened and an increase in free volume.…”
Section: Conductivity Measurementssupporting
confidence: 83%
“…This has also seen by other workers, e.g. [46]. The cables were obviously oxidised and the increase in conductivity may be due to the molecular bonds being weakened and an increase in free volume.…”
Section: Conductivity Measurementssupporting
confidence: 83%
“…In Figure 5, the effect of ageing on cables without an outer semicon layer can be observed. The color of the XLPE insulation layer changed from translucent grey to a rich, less transparent, brown, which is presumably indicative of thermo-oxidative degradation likely to occur under these circumstances [10]. It has been reported that, as well as an expected change in coloration, this ageing may lead to an increase in free volume and the mobility of charge carriers [10].…”
Section: Samplesmentioning
confidence: 99%
“…[23][24][25] With the rise of aging temperature, the molecular movement of the polymer chains intensifies, the viscosity reduces and the conductivity increases significantly. Meanwhile, the antioxidant is gradually consumed and the cross-linking degree decreases, then ε and ε increase as a whole.…”
Section: B Test Results and Analysis Of Thermal Aging In The Range Omentioning
confidence: 99%
“…Meanwhile, the antioxidant is gradually consumed and the cross-linking degree decreases, then ε and ε increase as a whole. [23][24][25][26] When the electric field frequency is very low, the carriers in XLPE would accumulate at the interface and in the defects and form the interfacial polarization. In addition, there are many factors influencing the XLPE dielectric constant, such as the steering of the molecular chain, the fracture of the macromolecular chain, the dipole turn formed by oxidation, and the ion displacement polarization caused by the ionization of impurities, which are generated by the alternating electric field.…”
Section: B Test Results and Analysis Of Thermal Aging In The Range Omentioning
confidence: 99%
See 1 more Smart Citation